2021
DOI: 10.3390/jpm11090849
|View full text |Cite
|
Sign up to set email alerts
|

Peri- and Post-Menopausal Women with Schizophrenia and Related Disorders Are a Population with Specific Needs: A Narrative Review of Current Theories

Abstract: Background: While gender differences in antipsychotic response have been recognized, the potential role of menopause in changing drug efficacy and clinical outcome in schizophrenia related disorders has been understudied. We aimed to review the relevant literature to test whether optimizing menopausal and post-menopausal treatment and addressing specific health needs of this stage in life will improve outcome. Methods: Non-systematic narrative review using the PubMed database (1900–July 2021) focusing on rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Risperidone has a mean QTc increase of 9.1 ms, and causes QTc prolongation via actions on IKr channels, with a similar potency as haloperidol [ 16 ]. Still, the risk is much lower than haloperidol and thioridazine [ 13 , 18 , 21 ]. Table 1 summarizes the antipsychotics discussed here, the associated cardiac events, and the mechanism by which these events could happen.…”
Section: Cardiac Issues and Antipsychoticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risperidone has a mean QTc increase of 9.1 ms, and causes QTc prolongation via actions on IKr channels, with a similar potency as haloperidol [ 16 ]. Still, the risk is much lower than haloperidol and thioridazine [ 13 , 18 , 21 ]. Table 1 summarizes the antipsychotics discussed here, the associated cardiac events, and the mechanism by which these events could happen.…”
Section: Cardiac Issues and Antipsychoticsmentioning
confidence: 99%
“…Age and the onset of menopause can lead to an increase in antipsychotic adverse effects. With the onset of menopause, estrogen levels drop, which studies have shown to lead to the worsening of hallucinations and delusions during this time [ 13 ]. This may necessitate the need for increased dosages of antipsychotic doses, which can lead to increased adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…The menopausal transition is marked by the loss of the neuroprotection conferred by estrogens during the reproductive period, leading to psychiatric exac erbations [51]. Antipsychotic doses often need to be adjusted and women show inferior responses to antipsychotics than during premenopause [52 ▪▪ ], which may worsen medical comorbidities. Estrogen receptor modulators, such as raloxifene, have been effectively added to treatment with antipsychotics allowing to decrease their doses, which results in lower risk for metabolic and cardiovascular side effects [39].…”
Section: Perimenopausementioning
confidence: 99%
“…In general, these studies showed that the stages of the positive reaction in female animals and improvement of symptomatic in women were higher [13], though the level of the expression of extrapyramidal symptoms was also higher [22,39]. As some authors say [17,22,27,32,34,35], young women with schizophrenia require less doses of the first-generation antipsychotics than men. Authors think that it can be explained either by a smaller body mass in women (younger than 40 years old), or by the fact that after the menopause women more often require even higher doses of antipsychotics than men.…”
Section: Socialmentioning
confidence: 99%